THE STRATEGIES FOR INCREASING CUSTOMER SATISFACTION PERFORMANCE OF THE COMPANY PT AJAIB SEKURITAS ASIA - Tambunan, John Christian P. (Bajang Institute, 2025)
Abstract. Growing levels of financial literacy and public investment create a large market potential for investment products, one of which is stock investment. Moreover, currently in Indonesia the number of Indonesian capital market investors is still around 5 million SID (Single Investor Identification). Compared with developed countries, Indonesia is quite far behind. Like Singapore, where 26% of the people are investors in their capital market. This research aims to analyze the influence of e-service quality, brand and digital marketing, on improving company performance and satisfaction with its use. The number of respondents used in this research was 75 respondents. This research uses quantitative and qualitative (mixed) research methods. The sampling technique uses the Structural Equation Modeling Method proposed by Joseph F. Hair. Data collection uses questionnaires. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed with Smart PLS 4.0 for quantitative analysis, while for qualitative analysis uses SWOT, IFE & EFE and QSPM. The author also conducted a Forum Group Discussion with the Main Director and Management of PT Ajaib Sekuritas Asia.